Research Joint Ventures, Optimal Licensing, and R&D Subsidy Policy - Cuihong Fan; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
We reconsider the justifications of R&D subsidies by Spencer and Brander (1983) and others by allowing firms to pool R&D investments and license innovations. In equilibrium R&D joint ventures are formed and licensing occurs in a way that eliminates the strategic benefits of R&D investment in the subsequent oligopoly game. Nevertheless, governments subsidize their domestic firms in order to raise their bargaining position in the joint venture. This holds true regardless of whether governments offer either unconditional or conditional subsidies. This suggests an alternative explanation of the observed proliferation of R&D subsidies.
urn:nbn:de:bvb:19-epub-13386-3
Keywords: L13; O34; 330; patent licensing; industrial organization; R&D subsidies; research joint ventures; technology policy